Aribah Trading - Sangkar, Mohd Guntur; Moriga, Jess Joel; Patinin, Mohd Zharif Syamil; Louis, Shawn Franklin (2017)
Aribah Trading is about produce, supplying and selling natural stomach pain medication only based on guava's leaves. Our business is located at Adnan Shopping complex, Block A, First Floor, 89008, Keningau, Sabah. While there are many stomach pain medication everywhere, Aribah Trading aim to produce 100% natural stomach pain medication based on guava's leaves. We will surely can compete in the market especially in Malaysia because of the traditional belief that guava's leaves can be utilize as a traditional medication for stomach. Moreover, we want to prevent the side effects of using stomach pain medication. Side effects usually happened when there are two or more chemicals react to each other. By using our product, it can be prevent because of our product is 100% natural without any add on chemical ingredient. Other than that, these leaves contain a number of beneficial substances, including antioxidants like vitamin C and flavonoids such as quercetin. The leaves can be utilize and be beneficial in treating diarrhea. We believe that our product can compete in the market and surely gain profit in the market because the needs of effective medicine for stomach pain.